2013
DOI: 10.14723/tmrsj.38.253
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Photonic Properties of Copolymers Containing Indolocarbazole Moiety in the Side Chain

Abstract: In this study, the synthesis of an indolo [3,2-b]carbazole (INC) derivative containing an octyl group and a pvinylbenzyl group at N-positions was carried out as a monomer compound to obtain copolymers with methyl methacrylate (MMA) by a radical polymerization. These copolymers showed the amorphous state and exhibited the higher thermal stability as INC content increased, which maintained the high emission property of INC moiety. Furthermore, the spin-coating and casting films could be prepared form the copolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Interestingly, PA-4 which possessed the long bisphenol-A unit in the diamine component exhibited the highest intensity of emission. Akimoto et al described that the photoluminescence intensity of INC containing copolymer solutions increased as the INC content decreased, because of the concentration quenching caused by the condensation of intermolecular interactions derived from INC components [8,10,11]. Namely, it was suggested that the photoluminescence intensity of INC-containing polyamides would be affected by weight percentage of INC content.…”
Section: Photonic Properties Of the Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, PA-4 which possessed the long bisphenol-A unit in the diamine component exhibited the highest intensity of emission. Akimoto et al described that the photoluminescence intensity of INC containing copolymer solutions increased as the INC content decreased, because of the concentration quenching caused by the condensation of intermolecular interactions derived from INC components [8,10,11]. Namely, it was suggested that the photoluminescence intensity of INC-containing polyamides would be affected by weight percentage of INC content.…”
Section: Photonic Properties Of the Polymersmentioning
confidence: 99%
“…In our previous study, the preparations of several polymers containing INC moiety in the main chain or side chain were investigated and the thermal and photonic properties of these polymers were estimated [8][9][10][11]. 1-(4vinylbenzyl)-7-octylindolo[3,2-b]carbazole (VINC-C8), and the copolymers of VINC-C8 with styrene or methyl methacrylate were prepared by a radical polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, the preparations of several polymers containing INC moiety in the main chain or side chain were investigated and the thermal and photonic properties of these polymers were estimated [8][9][10][11][12]. 1-(4-vinylbenzyl)-7-octylindolo [3,2-b]carbazole (VINC-C8), and the copolymers of VINC-C8 with styrene or MMA were prepared by radical polymerizations, and the thermal and photonic properties were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Akimoto et al described that the photoluminescence intensity of INC containing polymer solutions increased as the INC content decreased, because of the concentration quenching caused by the condensation of intermolecular interactions between INC components [8,10,11]. Therefore, to investigate the effect of INC concentration on the photoluminescence intensity, UV-Vis absorption and photoluminescence spectra of PAAINC were measured with changing the concentrations of polymer solutions, as shown in Figure 1(c) and (d).…”
mentioning
confidence: 99%